Implementasi Program Pengenalan Lapangan Persekolahan (PLP) dalam Pengembangan Kompetensi Sosial dan Profesional Calon Guru PAUD - Baiq Melinda Apriliani; I Wayan Karta; Aulia Dwi Amalina Wahab (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe the implementation of the School Field Introduction Program (Program Pengenalan Lapangan Persekolahan/PLP) in developing the social and professional competencies of prospective Early Childhood Education (PAUD) teachers. The study employed a qualitative approach with a descriptive research design and was conducted at three partner PAUD institutions, namely TK Al-Banna, TK DWP Dikpora Ampenan, and TK Nurul Iman Sekarbela. Data were collected through observation, interviews, and documentation. The data analysis process involved data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of PLP included observation activities, teaching assistance, and guided teaching practice. The program contributed to the development of students’ social competencies, as reflected in their communication skills, collaboration, empathy, and adaptability within the school environment. In addition, PLP also played a significant role in enhancing students’ professional competencies, particularly in mastering learning materials, planning and implementing instruction, classroom management, and understanding child development assessment. Based on the findings, it can be concluded that the School Field Introduction Program (PLP) plays an important role in preparing university students to become prospective PAUD teachers with strong social and professional competencies.